MANOVA: POWER ANALYSIS OF MODELS OF SUDOKU SQUARE DESIGNS - Shehu, A.; Dauran, N. S. (FUDMA JOURNAL OF SCIENCES, 2020)
This paper assesses the performance of multivariate treatment tests (Wilkâ€™s Lambda, Hoteling-lawley, Royâ€™s largest root and Pillai) on multivariate Sudoku square design models in terms of power analysis. Monte carlo simulation was conducted to compare the power of these four tests for the four multivariate Sudoku square design models. This study used  0.062 as interval value for Power difference between two tests of the same sample size. The test is considered powerful or having advantage, if the difference between the powers of the tests is   . The results of Power test show that Hoteling-lawley has advantage over three other tests at P=2 while at P=3 Wilkâ€™s lambda test has power advantage over other tests in all the multivariate Sudoku models.